Glycosylated whey protein isolate enhances digestion behaviors and stabilities of conjugated linoleic acid oil in water emulsions. (30th July 2022) - Li, Meng; Liu, Yue; Zhao, Jiale; Yu, Rui; Altaf Hussain, Muhammad; Qayum, Abdul; Jiang, Zhanmei; Qu, Bo
Highlights: Glycosylated protein made emulsion show better physical and oxidative stabilities. Glycosylated protein of 4 h showed the best physical stability of emulsion. Glycosylated whey protein isolate enhances digestion behaviors. Abstract: Although conjugated linoleic acid (CLA) has various excellent physiological functions, it exhibits poor water solubility and high oxidation sensitivity, which limits its applications in food industry. To solve this problem, a stable oil in water emulsion was used for protecting CLA. In this study, glycosylated whey protein isolate (GWPI) formed by whey protein isolate (WPI) and galactose was used to produce CLA emulsion, and then its physicochemical stabilities, gastrointestinal behaviors were evaluated. The results showed that creaming index, primary oxidation products and secondary oxidation products of GWPI-stabilized emulsion at reaction time of 4 h (GWPI-4 h) decreased by 32.43%, 95.98% and 87.34% when stored for 15 days, compared with WPI-loaded CLA emulsion. Additionally, GWPI promoted lipid digestion and led to an improvement of stability and gastrointestinal fate of GWPI-stabilized CLA emulsion. These findings confirmed that GWPI established an emulsification-based delivery system for protecting CLA to exert its physiological functions.